+0  
 
0
93
1
avatar

The function $f(n) = 3f(n-2) - 2f(n-1)$, where $f(2) = 3$ and $f(1) = -1$. What is the value of $f(5)$?

 Feb 28, 2020
 #1
avatar+30663 
+5

If  f(n) = 3f(n-2) - 2f(n-1)   and

f(1) = -1

f(2) = 3

We can simply continue:

f(3) = 3f(3-2) - 2f(3-1) = 3*(-1) - 2*3 = -9

f(4) = 3f(4-2) - 2f(4-1) = 3*3 - 2*(-9) = 27

f(5) = 3f(5-2) - 2f(5-1) = 3*(-9) - 2*27 = -81

 

 

More generally:

f(n) = (-1)n*3(n-1)

 Feb 29, 2020
edited by Alan  Feb 29, 2020

25 Online Users

avatar
avatar
avatar
avatar
avatar